Black Butterflyz: a physical activity intervention to improve the health of Black women - Omni, Christal M. (Kansas State University, 2019)
Black women are disproportionately impacted by issues of obesity, cancer, hypertension, and a host of other chronic diseases. To exacerbate matters, 82% of this population reports being overweight and 53% report being obese. Of the aforementioned chronic diseases and BMI classifications, physical inactivity serves as a key modifiable risk factor to address these health disparities faced by Black women. The purpose of Black Butterflyz was to develop an evidence-based, culturally-relevant intervention to increase physical activity among Black women. Formative research was conducted to identify barriers impacting physical activity along with preferred methods of physical activity among this target population. Based on the findings, lack of African American female role models engaged in physical activity, lack of knowledge, and lack of social support rose to the surface as key barriers impacting Black women’s engagement in physical activity. Furthermore, walking was identified as the preferred method of physical activity. In order to move inquiry into action, the Black Butterflyz intervention was developed. Black Butterflyz, a culturally-tailored 26-week walking intervention, was developed to provide social support while increasing participants’ levels of physical activity. The first 13 weeks (Phase I) of this 26-week intervention was conducted by the lead researcher while the second 13-weeks (Phase II) was conducted by trained volunteers within Black Butterflyz. Participants completed pre- and post-intervention measures of physical activity, social support, autonomy, motivation, and mood. Black Butterflyz resulted in a significant increase in leisure time walking (Z=-2.7, p=.007), moderate-intensity leisure-time physical activity (Z=-2.3, p=.02), total leisure time physical activity (Z=-2.7, p=.006) and exercise specific social support from friends (t (44) =-3.13, p=.003). Additionally, increases in leisure time physical activity were associated with increases in mood (r=.307 p=.042). The Black Butterflyz findings identify a strong need to train Black women to become group exercise instructors so they may single handedly and simultaneously address the three identified barriers impacting physical activity engagement among Black women-1) they become the role model, 2) they have the knowledge about physical activity and can impart that wisdom upon their respective communities, and 3) their presence provides social support.
Keywords: Physical activity; Black women; Culturally tailored; Health disparities; Kwanzaa